Psycholinguistic Studies on Autism Language Disorder - Imas Komala; Yulinda Ari Wardani; Herman Herman; Ventje Jany Kalukar (Green Publisher Indonesia, 2025)
This study investigates language disorders in individuals with autism from a psycholinguistic perspective, focusing on the cognitive and social factors that affect language development. Language disorders are a defining feature of Autism Spectrum Disorder (ASD), hindering effective communication and social interaction. The research examines pragmatic difficulties, semantic challenges, and the cognitive processing issues that individuals with autism experience, particularly in understanding and producing language. Through a qualitative approach, this study explores the relationship between these language disorders and psycholinguistic interventions that aim to improve communication skills. The results highlight the significance of targeted interventions, such as speech therapy and social communication training, in enhancing the ability of individuals with autism to engage in social interactions. The study concludes that while language disorders in autism cannot be completely cured, appropriate therapeutic methods can significantly improve language skills and social interactions. The implications of this research suggest that a psycholinguistic approach to autism language disorders can provide deeper insights into effective intervention strategies and improve communication abilities for individuals with ASD.